Influence of Processing Conditions on the Mechanical Behavior and Morphology of Injection Molded Poly(lactic-co-glycolic acid) 85:15 - Melo, Liliane Pimenta de; Salmoria, Gean Vitor; Fancello, Eduardo Alberto; Roesler, Carlos Rodrigo de Mello (International Journal of Biomaterials, 2017)
Two groups of PLGA specimens with different geometries (notched and unnotched) were injection molded under two melting temperatures and flow rates. The mechanical properties, morphology at the fracture surface, and residual stresses were evaluated for both processing conditions. The morphology of the fractured surfaces for both specimens showed brittle and smooth fracture features for the majority of the specimens. Fracture images of the notched specimens suggest that the surface failure mechanisms are different from the core failure. Polarized light techniques indicated birefringence in all specimens, especially those molded with lower temperature, which suggests residual stress due to rapid solidification. DSC analysis confirmed the existence of residual stress in all PLGA specimens. The specimens molded using the lower injection temperature and the low flow rate presented lower loss tangent values according to the DMA and higher residual stress as shown by DSC, and the photoelastic analysis showed extensive birefringence.